The creation and development of an integrated nursing service within a rural community health team : an action research study : a thesis presented in partial fuflilment of the requirements for the degree of Master of Arts in Nursing at Massey University - Cornish, Margaret Elizabeth (Massey University, 1995)
This Action Research study, guided by the philosophy of Critical Social Science, was undertaken to facilitate District and Public Health Nurses working in a multidisciplinary team in a rural area to reflect on and change their practice. The goal was to explore the possibility of combing their two separate roles into one integrated role. The idea was initiated by management who anticipated that an integrated role would ensure survival of their nursing service in the competitive environment created by the New Zealand Health Reforms. The study resulted in planned participative change brought about by this nursing group. Analysis of the process increased knowledge about rural community nursing and showed that the research group created a local theory. Through their reflection the nurses isolated and related factors about their work. From this, they created a model that represented a combined nursing practice while retaining their specialist roles. Using this model the nurses planned strategies that they predicted would bring specific results. During action and evaluation, these strategies were tested and culminated in putting the emergent model into practice. The model has potential to be generalised to other community nursing groups. Analysis of data showed that many factors enhanced the change process. Observation revealed that some group dynamics also had potential to inhibit change. When analysed with the group, the nurses recognised that there was a relationship between these dynamics and their job structure, their socialisation as women and their indoctrination as nurses. It also highlighted differences between how these District and Public Health Nurses think about their work and their roles. This critical reflection increased their self understanding and ensured that any planned change was more likely to endure. For the participants, this study has resulted in a positive sense of the value of their work, a strong sense of group cohesion, a better co-ordinated communication network, and confidence in their ability to make decisions for themselves. This has, in turn, given them a stronger nursing representation within their team and organisation.
Keywords: Community health nursing; Nursing practice; New Zealand